Ulmus davidiana 60% edible ethanolic extract for prevention of pericyte apoptosis in diabetic retinopathy - Kim, Iljin; Seo, Jieun; Lee, Dong Hyun; Kim, Yo-Han; Kim, Jun-Hyung; Wie, Myung-Bok; Byun, Jun-Kyu; Yun, Jang-Hyuk (Frontiers in Endocrinology, 2023)
Diabetic retinopathy (DR) is a disease that causes visual deficiency owing to vascular leakage or abnormal angiogenesis. Pericyte apoptosis is considered one of the main causes of vascular leakage in diabetic retina, but there are few known therapeutic agents that prevent it. Ulmus davidiana is a safe natural product that has been used in traditional medicine and is attracting attention as a potential treatment for various diseases, but its effect on pericyte loss or vascular leakage in DR is not known at all. In the present study, we investigated on the effects of 60% edible ethanolic extract of U. davidiana (U60E) and catechin 7-O-β-D-apiofuranoside (C7A), a compound of U. davidiana, on pericyte survival and endothelial permeability. U60E and C7A prevented pericyte apoptosis by inhibiting the activation of p38 and JNK induced by increased glucose and tumor necrosis factor alpha (TNF-α) levels in diabetic retina. Moreover, U60E and C7A reduced endothelial permeability by preventing pericyte apoptosis in co-cultures of pericytes and endothelial cells. These results suggest that U60E and C7A could be a potential therapeutic agent for reducing vascular leakage by preventing pericyte apoptosis in DR.